53.8k views
2 votes
Solve the systems of equations using elimination.

Check your solution by solution it back into the system.
1. 2x - 3y = -4
4x + 3y = 10

HELPPP

User Jack Billy
by
5.3k points

1 Answer

2 votes

Answer:

(1, 2 )

Explanation:

2x - 3y = - 4 → (1)

4x + 3y = 10 → (2)

Since the y-terms are opposites then adding the equations term by term will eliminate them.

6x = 6 ( divide both sides by 6 )

x = 1

Substitute x = 1 into either of the 2 equations and solve for y

Substituting into (2)

4(1) + 3y = 10

4 + 3y = 10 ( subtract 4 from both sides )

3y = 6 ( divide both sides by 3 )

y = 2

solution is (1, 2 )

User David Hobs
by
6.3k points